Business aspects along the rural-urban continuum, outlet type, and gender of ownership among MSMEs in the Vietnamese food environment - Ceballos, Francisco; Aguilar, Francisco; de Brauw, Alan; Nguyen, Trang; van den Berg, Marrit (International Food Policy Research Institute, 2025)
Concurrent with its rapid economic growth, Viet Nam has been experiencing a food systems transformation. Broad changes in the food environment have been a key part of this transition. While the availability of processed food is ubiquitous, the food environment continues to be largely dominated by micro, small, and medium enterprises (MSMEs). So, to build strategies to improve the availability and affordability of healthy foods, MSMEs are a key entry point. In this paper, we use primary survey data to separate key sources of variation in MSMEs’ organizational dimensions and business practices by type of outlet, rural-urban location, and gender of the owners. We focus on outcomes related to employment, food sources, business finance, good business practices, and nutrition knowledge and attitudes. We find limited differences in this set of outcomes in terms of whether an outlet is located in a rural, peri-urban, or urban area, or in terms of the gender of its owners. Instead, most of the variation in outcomes can be linked to the type of outlet, raising specific types of outlets as a key focus when seeking to foster the supply of healthier foods in the food environment.